ANALISIS FAKTOR PENGHAMBAT HAFALAN JUZ 30 SISWA (STUDI DI MI AL-HIDAYAH ROWOREJO, LAMPUNG BARAT) - Yati Anggraeni; Nur Hadi Kusuma (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study was motivated by the disparity between the tahfidz curriculum targets and the actual achievements of students at MI Al-Hidayah Roworejo, West Lampung, where the students’ high enthusiasm was not matched by their ability to complete the memorization of Juz 30. Key indicators of the problem include stagnation in memorizing long surahs, persistent pronunciation errors due to a lack of audio resources, and students’ psychological frustration stemming from the digital divide in rural areas. The objective of this study is to identify the determinants hindering the memorization of Juz 30 and to formulate a mitigation model relevant to local sociocultural characteristics. The research method used was qualitative with a phenomenological design, involving 20 informants consisting of students, teachers, and parents through purposive sampling. Data were collected through in-depth interviews, participatory observation over four weeks, and documentation, which were then analyzed using the Miles, Huberman, and Saldana interactive model. The findings and results of the study indicate that memorization barriers are multifactorial, including cognitive overload, limited access to digital technology, and weak domestic support due to the parents’ backgrounds, the majority of whom are farmers. As a practical recommendation, this study proposes a “Contextual Memorization Mitigation Model” that integrates adaptive offline-audio-based classroom management and the use of flexible memorization control cards that accommodate parents’ domestic work schedules. Synergy between madrasahs and families based on local wisdom has proven to be the key to maintaining students’ resilience and intrinsic motivation in memorizing the Qur’an.